A Case Study on Measuring Research Efficiency of Public Universities in Turkey - Ebru Yüksel Haliloğlu; Aslı Günay (Üniversite Araştırmaları Dergisi)
This paper measures the researchefficiency and productivity of public universities founded before 1981 inTurkey over theperiod 2013-2016. Data Envelopment Analysis is applied to assess the relativeresearch efficiency of these universities, while Malmquist Total FactorProductivity Index is used to measure the total factor productivity change withrespect to research inputs of universities. The analysis made here differ fromthe similar studies in terms of the diversity of data set and the measurementof university research efficiency and productivity changes together. Theresults indicate that the number of relatively efficient universities accordingto their reserach inputs declines continuously over the years. Also, theproductivity of research activities decreases except the period 2013-2014. Itis additionally observed that 2.3% fall in research productivity of theuniversities is due to deterioration in both technological and technicalefficiency over the yaers.